Jingles your company's secret weapon : secrets to winning customers through audio marketing! - DJ Fuzz 1977- (Mixology Music Sdn. Bhd., 2020)
This book will teach you how to use a jingle as and effective marketing tool that will make people remember your brand without emptying your pocket!